Design simulation of microstrip array antenna with low sidelobe level for synthetic aperture radar sensor - Alvissda Damai; Asrizal Asrizal; Yohandri Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2017)
The simulation of design of rectanglemicrostrip array antenna is presented in this paper. The proposed antenna is designed operate in 1.27 GHz (L-band) and consists of three element of the patch. The CST Studio Suite is employed in this simulation to optainethe low sidelobe level. This work aimed to produce the satisfyantenna characteristics for the SAR sensor. The low sidelobe level of the antenna is generated using Taylor Line Source method. Based on the simulation result, the antenna parameter such as S11, VSWR, impedansi (z) is -29.74 dB , 1.06, 50.05 ohm, respectively. the magnitude mainlobes = 11.3 dB and value side lobe level for Ө = -60o is 16.6 dB, and for Ө = 60o is 20.3 dB. The results of this simulation enough to fulfill characteristic antennae mikrostrip array with a lobes side greater than 15 dB.